THE EFFECT OF THEMATIC PATTERNING TECHNIQUE ON STUDENTS’ WRITING COMPETENCY OF TENTH GRADE STUDENTS AT SMAN 4 SINGARAJA - Astiti, N. T. K. K.; Marhaeni, A. A. I. N.; Suputra, P. E. D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
This study aimed at investigating whether there is a significant effect of the implementation of Thematic Patterning Technique on students’ writing competency of the tenth grade students at SMAN 4 Singaraja.  This is an experimental research.  The population of this study was the tenth grade students. There were two classes, consist of 75 students who were chosen as the samples of the study. Random sampling was used in order to find out the Experimental group and the Control group. This study was designed Posttest Only Non Equivalent Control Group design. The results of the posttest were analyzed descriptively and inferentially. Moreover, the results found that there was a significant difference of implementing thematic patterning technique on students’ writing competency of tenth-grade students at SMAN 4 Singaraja since, the students who were taught by using thematic patterning technique got higher score than students who were taught by using conventional technique (inquiry). Keywords: Thematic Patterning Technique, Writing